Inspiration After Posterior Pharyngeal Flap Palatoplasty: A Preliminary Study Using Computational Fluid Dynamic Analysis - Yang, Chao; Li, Jiang; Li, Huo; Chen, Nan; Yin, Xing; Shi, Bing; Li, Jingtao; Huang, Hanyao (Frontiers in Pediatrics, 2022)
Posterior pharyngeal flap palatoplasty (PPF) is one of the most common-used surgical procedures to correct speech, especially for patients suffering from velopharyngeal insufficiency (VPI). During PPF, surgeons use the catheter to control the lateral velopharyngeal port on each side. Airway obstruction and sleep apnea are common after PPF. To understand the air dynamics of the upper airway after PPF, we used computational fluid dynamics (CFD) to demonstrate the airflow. We had revealed the expiration process of the upper airway after PPF and showed the features of how PPF successfully restores the oral pressure for speech in our previous study. In this study, we focus on examining the the inspiration process. Normal airway structures were included. For normal velopharyngeal structure, one cylinder was applied to each model. For recapitulating the velopharyngeal structure after PPF, two cylinders were used in each model. The ports for borderline/inadequate closure, which can help the oral cavity get the required pressure, were chosen for this study. Real-time CFD simulation was used to capture the airflow through the ports. We found that the airflow dynamics of the upper airway's inspiration were dependent on the velopharyngeal structure. Although the airflow patterns were similar, the velocities between the one-port and two-port structures were different, which explained why patients after PPF breathed harder than before and suggested a one-port structure might be a better choice for secondary VPI reconstruction based on the CFD analyses.